2023
DOI: 10.4049/jimmunol.2200638
|View full text |Cite
|
Sign up to set email alerts
|

Immunogen-Specific Strengths and Limitations of the Activation-Induced Marker Assay for Assessing Murine Antigen-Specific CD4+ T Cell Responses

Abstract: The activation-induced marker (AIM) assay is a cytokine-independent technique to identify Ag-specific T cells based on the upregulated expression of activation markers after Ag restimulation. The method offers an alternative to intracellular cytokine staining in immunological studies, in which limited cytokine production makes the cell subsets of interest difficult to detect. Studies of lymphocytes in human and nonhuman primates have used the AIM assay to detect Ag-specific CD4+ and CD8+ T cells. However, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…They secrete cytokines IL-21 and IL-4, which work together with the co-stimulatory molecule CD40L to provide the signals required for B cell proliferation and differentiation (Crotty, 2015 ; Streeck et al, 2013 ). Cytokine-independent activation-induced marker (AIM) assay has been developed for antigen-specific GC Tfh cells in lymphoid tissue (Dan et al, 2016 ; Nguyen et al, 2023 ; Reiss et al, 2017 ). Our results showed that HA@PPCDQ induced a higher frequency of GC Tfh (CXCR5 + PD1 + ) and HA-specific GC Tfh (CD25 + OX40 + ) cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…They secrete cytokines IL-21 and IL-4, which work together with the co-stimulatory molecule CD40L to provide the signals required for B cell proliferation and differentiation (Crotty, 2015 ; Streeck et al, 2013 ). Cytokine-independent activation-induced marker (AIM) assay has been developed for antigen-specific GC Tfh cells in lymphoid tissue (Dan et al, 2016 ; Nguyen et al, 2023 ; Reiss et al, 2017 ). Our results showed that HA@PPCDQ induced a higher frequency of GC Tfh (CXCR5 + PD1 + ) and HA-specific GC Tfh (CD25 + OX40 + ) cells (Fig.…”
Section: Resultsmentioning
confidence: 99%